Fuerst-Bjeliš, B. and Glamuzina, N.: The Historical Geography of Croatia: Territorial Change and Cultural Landscapes - Vadas, András; Demeter, Gábor; Sokcsevits, Dénes (Hungarian Geographical Bulletin, 2021)
-